Особливості професійної Я-концепції патрульних поліцейських залежно від наявності попереднього досвіду роботи в МВС - Александров, Ю. В.; Aleksandrov, Y. V.; ORCID: http://orcid.org/0000-0002-5871-8344 (Право і безпека. – 2019. – № 1 (72). – С. 78-83, 2019)
Наголошено, що однією з важливих складових професіоналізації поліцейських (професіоналізація розглядається як цілісний безперервний процес становлення особистості фахівця, який починається з моменту вибору майбутньої професії) є формування сприятливої для ефективної професійної діяльності Я-концепції. Виходячи з нього, працю присвячено вивченню професійної Я-концепції патрульних поліцейських та особливостям цієї концепції залежно від наявності попереднього досвіду роботи в системі МВС України. Розкрито поняття Я-концепції, самооцінки, свідомості та самосвідомості особистості. Подано результати емпіричного дослідження, в якому взяли участь поліцейські, поділені на 2 групи – ті, які раніше служили в органах внутрішніх справ, і ті які не мали досвіду роботи в міліції. Під час дослідження вивчалися уявлення поліцейських про себе та про ідеал поліцейського, рівні самооцінки поліцейських, особливості їх кар’єрних орієнтацій та самоефективності.

The paper is focused to the study of the professional I-concept of patrol police officers and the features of this concept, depending on the availability of previous experience in the system of the Ministry of Internal Affairs of Ukraine. The definition of I-concept, self-appraisal, awareness and self-consciousness of a personality has been revealed. The modern approaches to the problem of the professional I-concept in psychology have been analyzed. The author has presented the results of the empirical study, which was attended by police officers divided into 2 groups – those who used to serve in the internal affairs agencies (IAA), and those who did not have experience in the militia. During the research the author has studied the representations of police officers about themselves and about the ideal police officer, the levels of self-appraisal of police officers, peculiarities of their career orientations and selfefficacy. It has been experimentally established that the self-appraisal of police officers without experience in the IAA is overestimated. The specifics of the system of representations of patrol police officers of different groups about their own professionally relevant personality qualities and the specifics of the system of representations about their own communicative qualities have been also researched. The author has demonstrated the vision by police officers who do not have the experience in the IAA, the image of an ideal patrol police officer, their understanding of the ideal police officer, as well as their vision of themselves as the bearer of leadership qualities, the attitude towards authoritarianism and dictatorial manifestations. Based on the research the author has also noted the specifics of career orientations and the peculiarities of the effectiveness of patrol police officers, depending on their previous experience in the police. To solve the problems, the author has used the following psycho-diagnostic techniques: “Personal differential”; Lyri method of diagnosis of interpersonal relations; “Career Anchors” by Edgar H. Schein; Scale of general self-efficacy; S. Budassi methodology.

Подчёркнуто, что одной из важных составляющих профессионализации полицейских (профессионализация рассматривается как целостный непрерывный процесс становления личности специалиста, начинающийся с момента выбора будущей профессии) является формирование благоприятной для эффективной профессиональной деятельности Я-концепции. Исходя из этого, работа посвящена изучению профессиональной Яконцепции патрульных полицейских и особенности этой концепции в зависимости от наличия предыдущего опыта работы в системе МВД Украины. Раскрыто понятия Я-концепции, самооценки, сознания и самосознания личности. Представлены результаты эмпирического исследования, в котором приняли участие полицейские, поделённые на 2 группы – те, которые ранее служили в органах внутренних дел, и те, которые не имеют опыта работы в милиции. Во время исследования изучались представления полицейских о себе и об идеале полицейского, уровни самооценки полицейских, особенности их карьерных ориентаций и самоэффективности.
Specific features of the professional i-concept of patrol police officers depending on the availability of previous experience in the Ministry of Internal Affairs
Особенности профессиональной я-концепции патрульных полицейских в зависимости от наличия предыдущего опыта работы в МВД
Александров, Ю. В. Особливості професійної Я-концепції патрульних поліцейських залежно від наявності попереднього досвіду роботи в МВС / Юрій Васильович Александров // Право і безпека. – 2019. – № 1 (72). – С. 78-83. – DOI: https://doi.org/10.32631/pb.2019.1.10.
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; патрульні поліцейські; Я-концепція; професійна Я-концепція; самооцінка самоефективності; професійний відбір; професіоналізація; самооцінка; свідомість особистості; самосвідомість особистості; комунікативні якості; patrol police officers; I-concept; professional I-concept; self-efficacy; self-appraisal; professional selection; professionalization; self-awareness; self-consciousness; communication skills; патрульные полицейские; Я-концепция; профессиональная Я-концепция; самооценка самоэффективности; профессиональный отбор; профессионализация; самооценка; сознание личности; самосознания личности; коммуникативные качества